5-Methyl ether flavone glucosides from the leaves of Bruguiera gymnorrhiza. (March 2015) - Panyadee, Acharawan; Sahakitpichan, Poolsak; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: Two new 5-methyl ether flavone glucosides, 7, 4′, 5′-trihydroxy-5, 3′-dimethoxyflavone 7- O -β-D-glucopyranoside and 7, 4′-dihydroxy-5-methoxyflavone 7- O -β-D-glucopyranoside were isolated from Bruguiera gymnorrhiza . Highlights: Two new 5-methyl ether flavone glucosides were isolated from Bruguiera gymnorrhiza . The aryl-tetralin lignan rhamnoside with negative optical rotation value was rare. This work provided the additional data of the polar compounds of the genus Bruguiera . Abstract: Two new 5-methyl ether flavone glucosides (7, 4′, 5′-trihydroxy-5, 3′-dimethoxyflavone 7- O -β-D-glucopyranoside and 7, 4′-dihydroxy-5-methoxyflavone 7- O -β-D-glucopyranoside) were isolated from the leaves of Thai mangrove Bruguiera gymnorrhiza together with 7, 3′, 4′, 5′-tetrahydroxy-5-methoxyflavone, 7, 4′, 5′-trihydroxy-5, 3′-dimethoxyflavone, luteolin 5-methyl ether 7- O -β-D-glucopyranoside, 7, 4′-dihydroxy-5, 3′-dimethoxyflavone 7- O -β-D-glucopyranoside, quercetin 3- O -β-D-glucopyranoside, rutin, kaempferol 3- O -rutinoside, myricetin 3- O -rutinoside and an aryl-tetralin lignan rhamnoside. The structure of a lignan rhamnoside was found to be related to racemiside, an isolated compound from Cotoneaster racemiflora, and also discussed. Structure determinations were based on analyses of physical and spectroscopic data including 1D- and 2D-NMR.